Parathyroid hormone-related protein-stanniocalcin antagonism in regulation of bicarbonate secretion and calcium precipitation in a marine fish intestine - Fuentes, J. (2010)
Parathyroid hormone-related protein-stanniocalcin antagonism in regulation of bicarbonate secretion and calcium precipitation in a marine fish intestine. Am J Physiol Regul Integr Comp Physiol 299: R150–R158, 2010. First published April 21, 2010; doi:10.1152/ajpregu.00378.2009.—Bicarbonate secretion in the intestine (duodenum) of marine fish has been suggested to play a major role in regulation of calcium availability for uptake. However, while the end process may lead to carbonate precipitation, regulation of transport of calcium and/or bicarbonate may actually result in fine-tuning of calcium availability for transport. To test this hypothesis, sea bream (Sparus auratus) duodenal preparations were mounted in Ussing-type chambers and the effect of parathyroid hormone-related protein (PTHrP) and stanniocalcin 1 (STC 1) on the control of intestinal bicarbonate secretion and calcium transport was analyzed. As expected, PTHrP increased net calcium uptake, as a result of an increase of calcium uptake without changes in calcium efflux. In contrast, purified sea bream STC 1 caused a minor decrease of calcium uptake and a two- to threefold increase in calcium efflux. As a result, STC 1 was able to invert the calcium flux from net calcium uptake to net calcium loss, which is in keeping with its known actions as a hypocalcemic factor. Furthermore, both PTHrP and STC 1 regulate intestinal bicarbonate secretion. PTHrP increased calcium uptake and simultaneously reduced the single factor that induces calcium precipitation, bicarbonate secretion. In contrast, STC 1, while reversing the calcium net flux to make it secretory, promoted intestinal bicarbonate secretion, both actions directed to decrease the calcium gradient across the epithelium and promote immobilization in the form of bicarbonate in the intestinal lumen. Together our results provide robust evidence to support an antagonistic action of PTHrP and STC 1 in the fine control of movements of both calcium and bicarbonate in the intestine of seawater fish.